Correlations Between Hypermobility, Muscle Strength and 3D Gait Parameters in Children With Increased Femoral Anteversion - EVRENDILEK, HALENUR (My University, 2019)
Introduction Increased femoral anteversion is a transverse plane problem that cause gait alterations in developing children and because of the moment arm changes produces muscle weakness around the hip (1). Especially, in addition with hypermobility, these children mostly have fatigue, additional muscle weakness and functional deterioration on lower extremity (2). Therefore, the aim of this study was to determine the relations between the hypermobility, muscle strength and gait parameters in children with IFA. Research Question Are there any correlation between the hypermobility, muscle strength and gait parameters in children with IFA? Methods 7 children with IFA (14 limbs, av.age: 9.14 ± 0.3, trochanteric prominens angle test (TPAT): 28 ± 6.2°) have participated in this study. As part of physical assessment; hypermobility, femoral anteversion angle, maximum isometric hip extensor and abductor, knee extensor and flexor muscles strengths were evaluated by Beighton test (3), TPAT (4) and hand-held dynamometer (HHD) (Lafayette Instruments,USA)(5) respectively. Furthermore, all participants' self-selected of walking were analyzed by 3D gait analysis (BTS Bioengineering). Kinematic gait parameters of pelvis, hip and knee were interested gait parameters. According to data distributions, Pearson's or Spearman's coefficient test were utilized for statistics (p<0.05) and interpreted by Cohen's classification (6). Results High-level correlation was found between Beighton scores and both hip extensor (r: -.70) and knee extensor (r: -.91) muscle strengths, and mean and minimum knee knee flexion angles. TPAT was highly correlated with only hip abductor HHD scores and mean hip rotation angle during walking (Table 1). Discussion In the literature, number of gait alterations were determined in children with IFA as increased mean hip internal rotation, pelvic obliquity range, peak knee extension at stance(7). The present study revealed that some of the kinematic alterations might be related to muscle strengths of the weak hip extensor and abductor, knee extensor and flexor muscles. Although, in agreement with the literature the mean hip internal rotation and hip abductors muscles strength were found significantly related to TPAT. In additionally, hypermobility, which is a commonly seen with the children with IFA, might have a role at the weakness of the hip and knee extensors and hyperextension at stance phase. In conclusion, it is important to strength hip extensor and abductor, knee extensor and flexor muscles to contribute to lower extremity function in children with IFA especially if the child is hypermobile.